PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT BERBANTUAN MEDIA PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN KONSENTRASI DAN HASIL BELAJAR (Studi pada Mata Pelajaran IPA Siswa Kelas VII SMP Negeri 10 Lahat) - Des Syukurti (DIADIK, 2020)
This research aims to improve the concentration and student learning achievement of the implementation of cooperative learning model team games tournament Type with a media snakes game. Research subject of  classroom action research (CAR) and quasi-experiment. This CAR is carried out in three cycles. The research subjects for this class action research were students of class VI of SMP Negeri 10 Lahat. Data collection techniques used were observation and tests. The data obtained were analyzed using the average formula and the interrelated t test and the unconnected t test. The results of this study indicate that the application of cooperative learning models of team games tournament assisted by snakes and ladders game can improve the concentration and learning outcomes of Grade VII students of SMP Negeri 10 Lahat so that it can be used in science learning.